Curcumin prevents diabetic cardiomyopathy in streptozotocin-induced diabetic rats: Possible involvement of PKC–MAPK signaling pathway - Soetikno, Vivian; Sari, Flori R.; Sukumaran, Vijayakumar; Lakshmanan, Arun Prasath; Mito, Sayaka; Harima, Meilei; Thandavarayan, Rajarajan A.; Suzuki, Kenji; Nagata, Masaki; Takagi, Ritsuo; Watanabe, Kenichi (European journal of pharmaceutical sciences, 2012)
The development of diabetic cardiomyopathy is accompanied with a high membrane-bound protein kinase C (PKC) levels. Curcumin is a naturally occurring compound which is known to inhibit PKC activity. However, the effects of curcumin on ameliorating diabetic cardiomyopathy are still undefined. We evaluated whether curcumin treatment is associated with the modulation of PKC-α and -β2-mitogen-activated protein kinase (MAPK) pathway in experimental diabetic cardiomyopathy. Diabetes was induced in male Sprague–Dawley rats by streptozotocin (STZ). Curcumin (100mg/kg/day) was started three weeks after STZ injection and was given for 8weeks. We demonstrate that curcumin significantly prevented diabetes-induced translocation of PKC-α and -β2 to membranous fraction and diabetes-induced increased phosphorylation of p38MAPK and extracellular regulated-signal kinase (ERK)1/2 in left ventricular tissues of diabetic rats. Curcumin treatment also markedly decreased NAD(P)H oxidase subunits (p67phox, p22phox, gp91phox), growth factors (transforming growth factor-β, osteopontin) and myocyte enhancer factor-2 protein expression as well as inhibited NF-κB activity at nuclear level. Furthermore, curcumin decreased the mRNA expression of transcriptional coactivator p300 and atrial natriuretic peptide, decreased accumulation of ECM protein and reversed the increment of superoxide production in left ventricular tissues, as evidenced by dihydroethidium staining. It is also significantly lowered plasma glucose and attenuated oxidative stress, as determined by lipid peroxidation and activity of anti-oxidant enzyme, and as a result attenuated cardiomyocyte hypertrophy, myocardial fibrosis and left ventricular dysfunction. Taken together, it is suggested that curcumin by inhibiting PKC-α and -β2-MAPK pathway may be useful as an adjuvant therapy for the prevention of diabetic cardiomyopathy.